Slavery and Post-Abolition in Ceará: memories and trajectories of liberated populations in the city of Redemption - Santos Gomes, Arilson dos (Revista Crítica Histórica, 2022)
Redemption, located in the Region of the Baturité Massif, is considered the symbol city of abolition in the State of Ceará. In the municipality, the liberation of the enslaved occurred in 1883, five years before the Aurea Law of 1888. From the investigations about the descendants of freedpeople in the region, and through the use of oral sources, in the light of the concepts of memory and collective memory (HALBWACHS, 1990; POLLAK, 1989), thematic and life histories were conducted (ALBERTI, 2005). The intention was to assist in understanding the possible destinies of the liberated populations, in Redemption, after abolition.